Analisis Perilaku Pondasi Tiang Helical Pada Tanah Gambut Menggunakan Metode Finite Element - Riady, Azhar; Yusa, Muhammad; Fatnanta, Ferry (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
The study related to the determination bearing capacity of helical pile in peat soil has been conducted previously. This study is costly and requires an extra effort, thus it is necessary to find another approach to determine bearing capacity of helical pile. In this study helical pile was modelled using finite element method of Optum G2 application program which aimed to estimate bearing capacity. The program is easily accessible, relatively simple to use and provide a wide variety of examples related geotechnical engineering problem. Peat soil was modelled based on Mohr coulomb criteria and the helical pile is classified as LL helical pile which modelled in this study. Determination of bearing capacity of helical pile was done by comparing the settlement between the results of the field finding and the computation using Optum G2. The settlement in this study consist of the two types of settlements, loading and unloading. The results from modelling indicated that settlement in loading test are similar to those on the field tests. However, for unloading test there is a difference between field test and modelling. This suggest that the model of Mohr coulomb criteria is inapplicable for the peat soil. Keywords : Helical Pile, Peat Soil, Finite element method, Soil nailing, Optum G2